Software quality model for a research-driven organization-An experience report - Wolski, Marcin; Walter, B.; Kupinski, S.; Chojnacki, J. (2017)
© 2017 John Wiley & Sons, Ltd. In the paper, we present a measurement framework for evaluating quality in software products developed within the research and innovation framework project GÉANT. The proposed framework is based on the quality models by Boehm and McCall, but also addresses the presence and point of view of a third stakeholder: an external funding agency (EU), which has started and is temporally financing the project, but aims at making it self-financing in the future. We also provide results of evaluation of 2 projects from the GÉANT ecosystem and one open-source system with this framework.